Produção de variedades de alface sob diferentes potenciais de água no solo em ambiente protegido - Maggi, Marcio Furlan (2006)
The knowledge of meteorological elements in protected environment is very important for commercial plants, because of possibility to produce for all the year according to the study conduced in Botucatu - SP, in order to evaluate the effects of different irrigation treatments on three lettuce cultivars. (Lisa, Crespa and American). The study was developed in a polyethilene tunnel with orientation northeast/southwest (NE/SW) and the fertigation through drip irrigation. Leaf number, head diameter, fresh weigh, dry weigh, meteorological elements and evaporation from minievaporimeters were determined. Four treatments of minimum soil water potential were applied: 20, 28, 35 and 45 kPa and the results showed the treatment -35 kPa showed the highest lettuce production and maximurn water efficiency use. The highest productions occurred in May/June, July/September and September/November, while the worst one was in February/April. There was not significant difference of dry mass production among the treatments, independently of the year period with exception of the Crespa cultivar which was superior in September/November. The south face showed the highest evaporation.